EFL Apps Potential Unleashed: Enhancing Pre-service Teachers' Digital Literacy via Tech-Vlog - Muslimin, Afif Ikhwanul (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
The aim of this research is to find out how effective English as a Foreign Language (EFL) technology video blogs are as a means of improving Digital Literacy (DL) before EFL services. This research uses sequential explanatory mixed methods, as well as a research design designed as survey and descriptive. Forty-three students in the English department of a state university in West Nusa Tenggara, Indonesia, took microteaching and technology-enhanced language learning (TELL) classes. Qualitative data was obtained from interviews and reflective journals, while quantitative data was obtained from digital literacy questionnaires. These results suggest that the technology video blog platform had a positive effect on participants' confidence in incorporating technology into their future classrooms. Participants reported that they had better skills in choosing the right apps, creating interactive activities, and encouraging students to become more digitally literate. This research found that technology video blog platforms are a promising tool for improving EFL pre-service teachers' digital literacy. These results emphasize how important it is to combine reflective practice and experiential learning to help pre-service teachers use EFL teaching applications effectively. These results will have an impact on teacher education programs because they will help future educators acquire the digital skills necessary to thrive in a technologically driven educational environment.Â